Small bowel transplantation – the latest developments. (May 2019) - Middleton, Stephen; Massey, Dunecan; Woodward, Jeremy; Sharkey, Lisa
Abstract: The UK has played a pivotal role in the development of intestinal transplantation to a procedure that is routinely offered to patients with complex intestinal failure and other life-threatening conditions. In the international Intestinal Transplant Registry's latest report, the overall survival figures were inferior to those expected for patients on parenteral nutrition (PN). However, in the better performing centres, survival figures for isolated intestinal transplantation are approaching those of PN, and good candidates for surgery might be offered the procedure as an alternative to PN if this trend continues. The more complex procedure to transplant multiple abdominal viscera including liver – multivisceral transplantation – is reserved for patients with an expected survival of less than a year without this procedure. Careful patient selection is important and has been enhanced by the National Adult Small Intestinal Transplant forum, which provides a national multidisciplinary review of patients considered as potential transplant candidates. The development of systems to estimate patient survival would enhance patient selection and allow more timely transplantation. This might also reduce late referral, which continues to contribute to mortality. Clinicians should consider referral of patients at an early stage to allow timely consideration of transplantation is also discussed.